On Using Profiles to Create Self-Organizing Peer-To-Peer Networks - HAAHR, MADS (IEEE, 2005)
Searching and organization of peers are fundamental challenges in P2P networks. Unstructured networks, such as Gnutella, inefficiently use broadcast searches and random neighbors. Structured networks are similarly inefficient, as they generally rely on globally unique identifiers (GUIDs) which are assigned irrespective of content, which prevents fuzzy semantic searches. In both types of network search, neighbors establish trust between themselves, regardless of whether or not their content is likely to satisfy searches. We present the idea of using contextbased profiles to describe peers. This enables selforganizing clusters of similar peers. A profile represents a peer?s expertise based on content and responsiveness. By refining the search process using these profiles, more efficient directed searches are possible. Moreover, expertise provides a basis for trust establishment.
PUBLISHED
Keywords: P2P